(untitled) (Research, Society and Development, 2021)
This course conclusion work proposes to analyze the actions taken by the Educational Advisor in the view of the Basic Education School professionals. Therefore, a semi-structured digital questionnaire was applied to elementary school teachers from public schools in the municipality of Parobé in the State of Rio Grande do Sul. Aiming to list the actions taken by educational advisors in the face of problems observed in the school context and identify how these actions can contribute or even harm the students’ teaching-learning process. Many teachers have doubts about the role of the Advisor and this makes it difficult for them to act with the students, since situations that would need their intervention may end up being neglected, as they are not taken to the Advisor. Finally, it was observed the importance of establishing a harmonious relationship between the subjects that make up the school community so that the work of all involved parties can be carried out in a more effective and satisfying way.